IDENTIFICATION OF THE DIFFERENCES OF TRADITIONAL MASSAGE AND SPORT MASSAGE - Purwanto, Didik; Kandupi, Ardiansyah D. (Journal Physical Education, Health and Recreation, 2023)
The need for massage among the public and athletes is increasing day by day. It is this increasing number of patients who need to be given education on the differences between traditional massage and sports massage. The purpose of this study was to identify the differences between traditional massage and sports massage for alumni of PJKR FKIP Tadulako University who have received sports massage courses and have opened a sports massage clinic. The research method used was qualitative research which was carried out in three stages: (1) the first stage was the approach stage and problem identification at the research location through interviews, (2) the second stage was conducting FGDs to equalize perceptions about massage and information sharing between traditional masseurs and alumni and lecturers of sports massage courses, and (3) the third stage, is data collection which is carried out by referring to the steps and techniques of data collection. The research was conducted in Palu City. The sample of this study were 4 traditional masseurs in Palu City and Poso Regency, Central Sulawesi with 4 alumni of PJKR FKIP Tadulako University who had attended massage courses (sport massage) and had opened a sports massage clinic and had also completed their undergraduate studies. The results of this study are that there are differences between traditional massage and sports massage which are quite striking in terms of the massage techniques and manipulation movements used, and in terms of techniques and where massage skills are obtained